Energy cost of biological nitrogen fixation - Neves, Maria Cristina Prata (International Center for Tropical Agriculture, 1982)
Biological nitrogen (N2) fixation in both free-living and symbiotic organisms is an energy-requiring process dependent upon a supply of carbon and energy. In this paper the energy costs for N2 fixation and nodule respiration in symbiotic systems are compared with those of free-living N2-fixing systems, with the theoretical energy requierement for N2 fixation, and with the cost of utilization of combined N.